Biochemical changes associated with gibberellic acid-like activity of smoke-water, karrikinolide and vermicompost leachate during seedling development of Phaseolus vulgaris L. Issue 1 (17th February 2014) - Singh, Satendra; Kulkarni, Manoj G.; Van Staden, Johannes
Abstract: Smoke-water (SW), karrikinolide (KAR1 ) and vermicompost leachate (VCL) have been reported to possess gibberellic acid-like activity. The effects of these plant growth-promoting substances (PGPSs) on biochemical changes occurring during seed germination of Phaseolus vulgaris were assessed. Seeds were incubated/germinated under dark conditions in water (control) or with different concentrations of SW, KAR1, VCL and gibberellic acid (GA3 ) for 7 d. The maximum seedling fresh weight (1.863 g) was recorded for the SW (1:750 v/v) treatment. The longest seedling axes (9.9 cm) and the highest number of adventitious roots (16.3) were recorded for VCL-treated seedlings (1:10 and 1:5 v/v, respectively). Analysis of two important hydrolytic enzymes, acid phosphatase and alpha-amylase, showed maximum activity [1856 nkat mg − 1 and 3.225 mg min − 1 (g FW) − 1, respectively] in the seeds incubated with 10 − 8 M KAR1 . In all the treated seedlings, proline content was significantly reduced [43.67 μg (g FW) − 1 ; VCL (1:20 v/v)] in comparison to the control [87 μg (g FW) − 1 ] but there was an increase in amino acids with some concentrations of PGPSs. The tested PGPSs significantly influenced various biochemical parameters that play a significant role in seed germination and plant growth. This study indicates that PGPSs may act via stress-relieving biochemical pathways during seed germination.